Uso de tecnologias assistivas no ensino de matemática em salas de recursos multifuncionais em uma rede municipal de ensino - Gubert, Larissa Leal Scapin (2022)
The teaching of Mathematics in an inclusive perspective has raised important debates and discussions, inside and outside school institutions. And, as allies for the teaching of this discipline, sometimes seen as challenging, especially for students of Specialized Educational Assistance, several Assistive Technologies emerge, so that this work can occur in an effective, inclusive, fair and adequate way for all students inserted in the educational context. In this context, the present research aimed to understand how the teachers of Multifunctional Resource Rooms, working in the early years of basic education in a municipality in the west of Paraná, are using Assistive Technologies for teaching Mathematics in their practice and which are the most used by the teachers. Fifteen teachers participated in the research, which had an exploratory character, and is based on a bibliographic survey of relevant references to the theme and a questionnaire prepared by the authors as an instrument for data collection. For data analysis, a qualitative approach based on the Discursive Textual Analysis technique was used. From the analysis, three main thematic categories emerged, namely: Multifunctional Resource Rooms and Inclusion; Mathematics and Multifunctional Resource Rooms; Assistive Technologies. The themes contributed to other secondary ones, from which it can be seen that the teachers recognized the Multifunctional Resource Rooms as a space and fundamental aid for the effectiveness of inclusion, and that the teaching of Mathematics in these environments occurs, most of the time, mainly through games and/or materials made by the teachers themselves. The study is relevant, as it seeks to contribute to what is being done by the teachers of these Multifunctional Resource Rooms and the possibility of learning new and different ways of teaching Mathematics to students of Specialized Educational Assistance.